First report of Cooperia curticei (Strongylida: Trichostrongylidae) in sheep from northwestern Argentina (FAVE Sección Ciencias Veterinarias, 2021)
Cooperia curticei is a nematode related to sheep that is housed in the small intestine. Its presence in Argentina has been reported in environments such as the semi-arid region in the Pampa, the sub-humid Pampas in Buenos Aires and in the subtropical region in Corrientes. The objective of this work is to report the presence of Cooperia curticei in the small intestine of a sheep from the town of Cerrillos in Salta. A worm burden of 600 adult forms of Cooperia spp. was determined in the small intestine. These were identified as Cooperia curticei. As relevant taxonomic features the branches of the dorsal ray curved backwards showing a lyre shape. As for the spicules, they measured an average of 146.8 µm (± 5.24), with a marked concavity in the middle part of the body and with a stem with a final curvature similar to a foot. This finding is the first of its kind in the NOA region and demonstrates the adaptation of C. curticei to a sub-Andean mountain type climate. This work complement that previously described in the region, where the presence of Cooperia spp. in sheep was described but without species determination.
Keywords: Ovine; Cooperia; Nematode; Salta